2017
DOI: 10.1016/j.ydbio.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

A defect in the mitochondrial protein Mpv17 underlies the transparent casper zebrafish

Abstract: The casper strain of zebrafish is widely used in studies ranging from cancer to neuroscience. casper offers the advantage of relative transparency throughout adulthood, making it particularly useful for in vivo imaging by epifluorescence, confocal, and light sheet microscopy. casper was developed by selective breeding of two previously described recessive pigment mutants: 1) nacre, which harbors an inactivating mutation of the mitfa gene, rendering the fish devoid of pigmented melanocytes; and 2) roy orbison, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 22 publications
4
85
1
Order By: Relevance
“…This metabolic fasting also activated transcriptional changes beyond gluconeogenesis genes and modulated other fasting adaptation pathways, such as β‐oxidation and cellular respiration, which drive ATP production in the mitochondria during low‐energy states (Houten, Violante, Ventura, & Wanders, ). A role for TSPO in regulating pigment patterning has not been uncovered, although changes in mitochondrial function and metabolic regulation have been noted to disrupt pigmentation in vertebrates (D'Agati et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This metabolic fasting also activated transcriptional changes beyond gluconeogenesis genes and modulated other fasting adaptation pathways, such as β‐oxidation and cellular respiration, which drive ATP production in the mitochondria during low‐energy states (Houten, Violante, Ventura, & Wanders, ). A role for TSPO in regulating pigment patterning has not been uncovered, although changes in mitochondrial function and metabolic regulation have been noted to disrupt pigmentation in vertebrates (D'Agati et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic lines used in these studies included wild-type ( AB ), casper (D'Agati et al, 2017;White et al, 2008) , and the triple line (Ceol et al, 2011) ( mitfa :BRAF V600E ; p53 -/-; mitfa -/-) (provided by the Houvras lab at Weill Cornell).…”
Section: Zebrafish Mutant Linesmentioning
confidence: 99%
“…The roy mutant shows a recessive phenotype with complete loss of iridophores and partial reduction of melanophores. Recent studies using cDNA cloning reported that mpv17 (a gene encoding a mitochondrial inner membrane protein) in casper and roy mutants had a 19-bp deletion in its mRNA (between exons 2 and 3), which is possibly responsible for the iridophore loss [7,8]. A mpv17-knockdown zebrafish exhibited a moderate loss of iridophores along the body axis [8].…”
Section: Introductionmentioning
confidence: 99%